Alcohol-Associated Bowel Disease (ABD) in a Young Patient Presenting with Mixed Gastrointestinal Bleeding: A Case Report - Agustien Bayu Ristanti; Muhammad Erlangga Putra Harimurti; Mohammad Amin Rais Perfernandi Ilham; Agastjya Wisjnu Wardhana (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2026)
Gastrointestinal (GI) bleeding is a common condition that can be life-threatening and requires prompt diagnosis and treatment. In younger adults without significant comorbidities, GI bleeding presents a diagnostic challenge, as it is uncommon and requires thorough evaluation to identify the underlying cause. Chronic excessive alcohol consumption is a significant yet often underrecognized risk factor. In recent studies, the term alcohol-associated bowel disease (ABD) has been introduced to describe GI problems mainly related to alcohol consumption. We present a case of a 29-year-old male with a history of chronic alcohol use who presented with melena and hematochezia. Laboratory evaluation revealed anemia and hypoalbuminemia, while abdominal ultrasonography revealed moderate fatty liver disease. Esophagogastroduodenoscopy confirmed erosive gastroduodenitis with a mucosal break greater than 5 mm, accompanied by esophageal candidiasis and grade B esophagitis. Meanwhile, colonoscopy confirmed the diagnosis of ulcerative colitis with active erosive ulcer bleeding. This case highlights severe mixed GI bleeding associated with chronic alcohol use, which may be classified as ABD. This case report aimed to demonstrate the importance of considering ABD in a relatively healthy young adult presenting with mixed and severe gastrointestinal bleeding